Life Cycle Ceremonies in Banjar Society: A Review of the Integration of Sunnah Values in Local Tradition - Nirwana, Dzikri; Saifuddin, Saifuddin; Hanafi, Hanafi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study examines the integration of Sunnah values and the interpretation of hadith in the life-cycle ceremonies of the Banjar community. Using the living Sunnah approach, it explores how local cultural elements are assimilated with Islamic teachings through the interpretation and application of specific hadiths. Employing field research and literature review methods, this study analyzes cultural adaptation in birth, marriage, and funeral ceremonies. Additionally, it investigates the role of scholars and the community in understanding and responding to hadiths that underlie these traditional practices. The findings highlight the dynamics of hadith acceptance and transformation within the local Banjar culture and its contribution to shaping the community's religious identity.